Travails of Vulnerable People in Accretion Site of Tagum City - Langcoy II, Roque N. (JPAIR Multidisciplinary Research, 2018)
The effort of the local government to answer the call for modernity and globalization in their respective locality gains investors' and capitalists' interest. It turns vast of lands into plantations (banana, palm oil, and pineapple) and subsequently changes the life of the people. The study aimed to explore the following: determine the demographic profile of the settlers in accretion site, and design an enhancement program. The study used an in-depth interview using a semi-structured questionnaire to gather data, using descriptive survey aided with researcher-made questionnaire employed to all 43 family settlers in accretion site. Results showed that most of the respondents are Christians, married, less educated, doing menial jobs to support their family and children, and have experienced colds, cough, fever, skin diseases, and dehydration. Moreover, the family respondents significantly showed interest in participating livelihood programs, to know about the prevention of communicable diseases, birth control, and raising children with good nutrition. This investigation concludes therefore that people become vulnerable in places where development happened due to less educational attainment, and they move to dangerous places to feed and earn a living for their families and children. But if given the chance people are willing to engage in activities that would help elevate their economic condition.
Keywords: Social Science; Vulnerable People; include accretion site Descriptive survey; Philippines